DETERMINANTS OF INDONESIAN BANKING PROFITABILITY - Achmad Saiful Ulum; Sholikha Oktavi Khalifaturofi'ah (Jurnal Riset Bisnis dan Manajemen, 2022)
This study aims to investigate determinants of Indonesian banking profitability. The determinants of banking profitability are bank specifics and macroeconomic indicators. This study uses balanced panel data involving 18 banks in Indonesia for the period 2009-2019. The research method used is panel regression method. Empirical findings indicate that bank specifics, such as bank liquidity and capital, have a positive and significant effect on banking profitability, while the cost-to-income ratio and leverage has a negative and significant effect on banking profitability. The results of this study have considerable implications for policy. The government needs to regulate inflation, exchange rates, and interest rates. The results of this study can help policy makers, governments, bankers, and bank managers to better understand the various determinants of bank profitability.